PELATIHAN PEMBUATAN WEB SEDERHANA DENGAN MENGGUNAKAN WORDPRESS DI MAN 4 MADIUN - Fardiana Karuniawati; Joko Triono; Sukadi; Tomi Tristono (JURNAL DAYA-MAS, 2026)
Studying informatics offers significant benefits for students, including improving critical thinking skills and enhancing hardware and software skills. MAN 4 Madiun collaborates with Merdeka Madiun University to enhance its students' skills using the school's resources. The D3 Manajemen Informatika provides training for students to introduce informatics, increase student interest in the field, and promote the study program by conducting simple website creation training using WordPress. This training was chosen because, based on observations, students were still unfamiliar with the web and the laboratory lacked of specific web application. This training can improve students' skills due to its ease of use and learning. The simple web training using WordPress at MAN 4 Madiun was successful and smooth. Students who participated in the training gained new knowledge about websites and gained new experiences in creating their own websites. Students also gained a better understanding of Merdeka Madiun University and the  D3 Manajemen Informatika Department.